Minimally important differences for interpreting European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 scores in patients with head and neck cancer. Issue 11 (6th July 2020) - Musoro, Jammbe Z.; Coens, Corneel; Singer, Susanne; Tribius, Silke; Oosting, Sjoukje F.; Groenvold, Mogens; Simon, Christian; Machiels, Jean‐Pascal; Grégoire, Vincent; Velikova, Galina; Cocks, Kim; Sprangers, Mirjam A. G.; et al.
Abstract: Background: We aimed to estimate minimally important difference (MID) for interpreting group‐level change over time for European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire core 30 (EORTC QLQ‐C30) scores in head and neck cancer. Methods: Data were derived retrospectively from two published EORTC trials. Clinical anchors were selected using correlation strength and clinical plausibility of the given anchor/QLQ‐C30 scale pair. MIDs for within‐group and between‐group change were estimated via the mean change method and linear regression, respectively. Distribution‐based MIDs were also examined. MIDs for two of the scales, dyspnea and nausea/vomiting, are more uncertain considering their low correlations with the anchors. Results: Anchor‐based MIDs could be determined for deterioration in 7 of the 14 QLQ‐C30 scales assessed, and in 3 scales for improvement. MIDs varied by scale, direction of change, and anchor. Absolute MID values ranged from 5 to 15 points for within‐group change and 4 to 12 for between‐group change. Most MIDs were within 4 to 10 points. Conclusions: Our findings, if confirmed, will aid interpreting changes in selected QLQ‐C30 scale scores over time and inform sample size calculations in future clinical trials in head and neck cancer.